A network pharmacology approach to explore active compounds and pharmacological mechanisms of epimedium for treatment of premature ovarian insufficiency - Zhao H; Shan Y; Ma Z; Yu M; Gong B (Dove Medical Press, 2019)
Huishan Zhao,1,* Yinghua Shan,1,* Zhi Ma,1 Mingwei Yu,2 Benjiao Gong31Reproductive Medicine Centre, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, People’s Republic of China; 2Department of Orthopaedics and Traumatology, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, People’s Republic of China; 3Central Laboratory, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, People’s Republic of ChinaCorrespondence: Huishan ZhaoReproductive Medicine Centre, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, People’s Republic of ChinaTel +86 1 861 597 9792Email zhaohuishan1011@163.comBenjiao GongCentral Laboratory, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, People’s Republic of ChinaTel +86 1 835 456 5136Email pumeigong@163.com*These authors contributed equally to this workBackground and purpose: Premature ovarian insufficiency (POI) refers to a hypergonadotropic hypoestrogenism and the condition of pre-onset ovarian function failure. Epimedium is a common traditional Chinese herbal medicine that is widely used to relieve POI in China. To systematically explore the pharmacological mechanism of epimedium on POI therapy, a network pharmacology approach was conducted at the molecular level.Methods: In this study, we adopt the network pharmacology method, which mainly includes active ingredients prescreening, target prediction, gene enrichment analysis and network analysis.Results: The network analysis revealed that 6 targets (ESR1, AR, ESR2, KDR, CYP19A1 and ESRRG) might be the therapeutic targets of epimedium on POI. In addition, gene-enrichment analysis suggested that epimedium appeared to play a role in POI by modulating 6 molecular functions, 5 cellular components, 15 biological processes and striking 52 potential targets involved in 13 signaling pathways.Conclusion: This study predicted the pharmacological and molecular mechanism of epimedium against POI from a holistic perspective, as well as provided a powerful tool for exploring pharmacological mechanisms and rational clinical application of traditional Chinese medicine.Keywords: network pharmacology, premature ovarian insufficiency, epimedium, infertility, GO, KEGG